Tree rings circle an abrupt shift in climate - Zhang, Qi-Bin; Fang, Ouya (Science (American Association for the Advancement of Science), 2020)
A recent drier-hotter climate stands out in the context of past climate variability An abrupt and substantial change in a climate system from one steady state to another—called a climate regime shift—has a considerable impact on ecosystems and society because of the abbreviated time period for adaptation ( 1 , 2 ). Recognizing the occurrence of regime shifts in climate is crucial for the timely development of effective policy responses to cope with the change. On page 1095 of this issue, Zhang et al. ( 3 ) reveal a recent regime shift to a drier and hotter climate throughout inner East Asia. The shift was detected with tree ring–based reconstructions of heat waves and soil moisture over the past 260 years.